Characterization of a 2-D Laser Scanner for outdoor wide range measurement. (November 2015) - Canciani, E; Vandone, A; Sala, R
Abstract: This paper presents a metrological characterization study of SICK LMS 511 laser scanner, with an extended analysis of its main acquisition issues. Various parameters that could affect the sensor performances, such as warm-up time, target properties (color and material), and target position (distance and orientation) are investigated. Moreover, the mixed pixel problem is introduced and, finally, since the sensor is designed to work in a wide outdoor environment, the effect of direct sun light is taken into account. Some cases of faulty data are identified and explanations discussed.